2007
DOI: 10.1177/1073858407309541
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from fMRI about Mapping Cortical Columns

Abstract: Recently-developed functional magnetic resonance imaging (fMRI) can map small functional structures non-invasively and repeatedly without any depth limitation. However, there has been a persistent concern as to whether the high-resolution fMRI signals actually mark the sites of increased neural activity. To examine this outstanding issue, we used iso-orientation columns of isofluraneanestheized cats as a biological model and confirmed the neural correlation of fMRI iso-orientation maps by comparing with intrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 75 publications
0
16
0
Order By: Relevance
“…Thus, unlike the late positive deoxy-Hb-weighted OIS (Fig. 2) or the decomposed deoxy-Hb signal (Malonek and Grinvald, 1996), the BOLD fMRI signal evoked by horizontal grating is larger than that evoked by vertical grating in iso-orientation domains for the horizontal grating (Kim and Fukuda, 2008;Moon et al, 2007). Additionally, the increase in both plasma blood volume and total-Hb content in the same iso-orientation domains suggests that arterioles rather than capillaries should be responsible for the column-specific blood volume regulation because capillaries do not seem to dilate to sensory stimulation (Chaigneau et al, 2003;Kleinfeld et al, 1998;Takano et al, 2006).…”
Section: Spatial Specificity Of Fmrimentioning
confidence: 88%
“…Thus, unlike the late positive deoxy-Hb-weighted OIS (Fig. 2) or the decomposed deoxy-Hb signal (Malonek and Grinvald, 1996), the BOLD fMRI signal evoked by horizontal grating is larger than that evoked by vertical grating in iso-orientation domains for the horizontal grating (Kim and Fukuda, 2008;Moon et al, 2007). Additionally, the increase in both plasma blood volume and total-Hb content in the same iso-orientation domains suggests that arterioles rather than capillaries should be responsible for the column-specific blood volume regulation because capillaries do not seem to dilate to sensory stimulation (Chaigneau et al, 2003;Kleinfeld et al, 1998;Takano et al, 2006).…”
Section: Spatial Specificity Of Fmrimentioning
confidence: 88%
“…Due to the indirect nature of the BOLD signal as a surrogate for neural activity, the spatial resolution of BOLD fMRI is a complex interplay between technical constraints (e.g., field strength, see Harel et al, 2006) that determine voxel size, physics (e.g., signal production as a function of sequence type and sensitivity to various vessel types and sizes, see Uludağ et al, 2009) and vascular point spread function (Menon and Goodyear, 1999;Sheth et al, 2004b;Harel et al, 2006;Shmuel et al, 2007;Yacoub et al, 2008;Kim and Fukuda, 2008). Thus, as pointed out by Harrison et al, 2002, further detailed mapping studies of blood pathways and associated control points are needed to estimate the ultimate spatial resolution of hemodynamic-based functional imaging methods such as fMRI.…”
Section: Hemodynamic Variations Induced By Local Vasodilationsmentioning
confidence: 99%
“…An fMRI study of the visual cortex demonstrated that accurate localization and resolution of the cortical columns could only be achieved when visual stimuli were kept relatively short [17]. In addition, other studies have suggested that appropriate task paradigms and activity quantification methods are required in order to evaluate the spatial resolution limits of BOLD fMRI [18,19].…”
Section: Introductionmentioning
confidence: 99%